Handbook of research on enterprise systems - Gupta, Jatinder N. D.; Sharma, Sushil K.; Rashid, Mohammad A. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
The advancement of computing and communication technologies have profoundly accelerated the development and deployment of complex enterprise systems, creating an importance in its implementation across corporate and industrial organizations worldwide. This handbook addresses the field of enterprise systems with more breadth and depth than any other resource, covering progressive technologies, leading theories, and advanced applications in over 25 articles from 47 expert authors from around the globe.